PENGEMBANGAN MATERI AJAR TEKS EKSPLANASI BERBANTUAN MEDIA ASSEMBLR EDU PADA SISWA KELAS VII UPT SMP NEGERI 2 MEDAN - Agnes Derma Yani, Anggi; Hutagalung, Trisnawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to determine the process of developing explanatory text teaching materials assisted by Assemblr EDU media for seventh grade students and the feasibility of the resulting product. This research is a development research (RnD) that uses the Borg and Gall development research procedure with stages a) potential and problems, b) data collection, c) product design, d) design validation, e) design revision. Product assessment was carried out by two experts, namely material experts and media experts. Data collection techniques used included observation, interviews with Indonesian language teachers, documentation and questionnaires to determine student needs. The research instruments used were student needs questionnaires and validation questionnaires from material experts, and media experts. The results showed that the product developed from the study